2009
DOI: 10.1534/genetics.109.102871
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Rice Blast Resistance Gene, Pid3, by Genomewide Comparison of Paired Nucleotide-Binding Site–Leucine-Rich Repeat Genes and Their Pseudogene Alleles Between the Two Sequenced Rice Genomes

Abstract: Rice blast, caused by Magnaporthe oryzae, is one of the most devastating diseases. The two major subspecies of Asian cultivated rice (Oryza sativa L.), indica and japonica, have shown obvious differences in rice blast resistance, but the genomic basis that underlies the difference is not clear. We performed a genomewide comparison of the major class of resistant gene family, the nucleotide-binding site-leucinerich repeat (NBS-LRR) gene family, between 93-11 (indica) and Nipponbare ( japonica) with a focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
129
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(148 citation statements)
references
References 60 publications
8
129
0
3
Order By: Relevance
“…Analyses of genes homologous to Pid3, one of the best-characterized rice blast resistance genes, showed that pseudogenization of Pid3 occurred after the divergence of indica and japonica (SI Appendix, Fig. S17), further supporting the findings in an earlier study (39). Comparative analysis of another important rice blast R gene, Pi-ta (40), suggests that the substitution from Ile to Ser at position 6 and subsequent replacement of Ser with Ala at position 918 created the Pi-ta protein that recognizes AVR-Pita in NIV (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 84%
“…Analyses of genes homologous to Pid3, one of the best-characterized rice blast resistance genes, showed that pseudogenization of Pid3 occurred after the divergence of indica and japonica (SI Appendix, Fig. S17), further supporting the findings in an earlier study (39). Comparative analysis of another important rice blast R gene, Pi-ta (40), suggests that the substitution from Ile to Ser at position 6 and subsequent replacement of Ser with Ala at position 918 created the Pi-ta protein that recognizes AVR-Pita in NIV (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 84%
“…An extensive study of the Pi-ta locus was reported from wild species of rice , cultivated (AA) and wild species (Lee et al 2009), and invasive weedy rice (Lee et al 2011). Another gene, Pid3 studied from 36 rice lines of both cultivated and wild species indicated pseudogenization of Pid3 in japonica cultivars (Shang et al 2009). Liu et al (2011) reported divergent selection in Pi9 locus cloned from cultivated and wild species of rice.…”
Section: Introductionmentioning
confidence: 99%
“…2); pi21 (Fukuoka et al, 2009) (Chr. 4); Pi-9 , Pi2 , Piz-t , Pid2 (Chen et al, 2006), Pid3 (Shang et al, 2009); Pi25 (Chen et al, 2011) (Chr. 6); Pi-36 ) (Chr.…”
Section: Allele Mining and Blast Resistance Genesmentioning
confidence: 99%
“…A similar situation was also seen in Pik, Pik-m, Pik-p, Pi1, Pi54 and Pi54rh (Ashikawa et al, 2008;Rai et al, 2011b;Yuan et al, 2011;Zhai et al, 2011;Das et al, 2012;Hua et al, 2012), which all reside on the same chromosome locus but are cloned independently from various varieties and show a differential level of resistance spectra to a collection of M. oryzae strains . Functional orthologs of the rice blast resistance gene Pid3 have been found primarily in most screened indica types and wild rice varieties (Shang et al, 2009). Lv et al, (2013) isolated an ortholog of Pid3 from a common wild rice accession A4 (O. rufipogon) using sequencingbased allele mining, called Pid3-A4, with confirmation of different amount of resistance spectra.…”
Section: Allele Mining and Blast Resistance Genesmentioning
confidence: 99%